Adjustment of surface energy on steel surfaces due to CLP generation by picosecond laser processing - Häfner, Tom; Heberle, Johannes; Holder, Daniel; Schmidt, Michael (Proc. Laser in Manufacturing Conference 2015, 2015)
With regard to mechanical and chemical resistivity metal surfaces can benefit from hydrophobic behavior. Against this background, results of laser-induced generation of hydrophobic surfaces on three different steel alloys without any additional coating are presented. Therefore, a dual-scale structure - consisting of micro cones and nano-ripples and droplets - is generated by picosecond laser structuring in ambient air. Firstly, the dependencies of the formation of these micro cones, called cone-like protrusions (CLP), on different parameters of the laser ablation process - the peak fluence, the spot diameter, the effective pulse number per unit area and the material - are investigated. Secondly, the hydrophobicity and surface energy of the resulting surface topography of the irradiated substrate are evaluated by means of contact angle measurements. For that purpose identical topographies are generated on stainless steel, hot- and cold-working steel. The time-dependency of the contact angle is investigated depending on the material and the morphology. For CLP formation a high number of scans is preferred to provide a high effective pulse number per unit area, which is advantageous for homogeneous generation of larger micro cones. By measuring the contact angle a change from an initially hydrophilic to a hydrophobic behavior of the surfaces can be observed due to a change of surface chemistry over time. Thus, contact angles higher than 90° can be measured on laser treated surfaces of different steel alloys.
Keywords: Micro processing; ablation

Speckle reduction techniques in holographic beam shaping for accurate and efficient picosecond laser structuring - Häfner, Tom; Heberle, Johannes; Holder, Daniel; Schmidt, Michael (Journal of Laser Applications, 2017)